Adopting the stranger as kindred in Deuteronomy - Glanville, Mark R. (Ancient Israel and its literature ;, 2018)
"Deuteronomy addresses social contexts of widespread displacement, an issue affecting sixty-five million people today. In this book Mark R. Glanville investigates how Deuteronomy fosters the integration of the stranger as kindred into the community of Yahweh. According to Deuteronomy, displaced people are to be enfolded within the household, within the clan, and within the nation. Deuteronomy demonstrates the immense creativity that communities may invest in enfolding displaced and vulnerable people, nourishing inclusivism through social law, law of judicial procedure, communal feasting, and covenant renewal texts. Deuteronomy's call to include the stranger as kindred presents contemporary nation-states with an opportunity and a responsibility to reimagine themselves and their disposition toward displaced strangers today"--